Efektivitas Pengelolaan Sarana dan Prasarana Pendidikan dalam Mewujudkan Lingkungan Sekolah yang Kondusif - Lulu Anggraini; Eva Marvira; Desy Eka Citra Dewi; Andhini Aprianti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The management of educational facilities and infrastructure is an important component in creating a conducive school environment for teaching and learning. Well-managed facilities and infrastructure can support learning activities, improve comfort, and foster a positive school climate. Therefore, it is important to examine the extent to which the effectiveness of facility and infrastructure management can contribute to the creation of a school environment that supports optimal student development. This study employs a qualitative approach using the case study method. Data collection was conducted through observation, in-depth interviews with the school principal, educators, and facility management staff, as well as relevant documentation. Data analysis was performed using data reduction techniques, data presentation, and conclusion drawing. The research findings indicate that effective management of facilities and infrastructure is characterised by thorough planning, regular maintenance, and the involvement of all school community members in maintaining the facilities. A clean, well-organised school environment with adequate learning facilities has a positive impact on students‘ motivation to learn, discipline, and teachers’ comfort in teaching. Thus, good management of facilities and infrastructure plays a significant role in creating a conducive school environment and supporting the achievement of educational goals.